The Research on Public Space in Colombia: its Importance to the Urban Management - Burbano Arroyo, Andrea Milena (Universidad del Rosario, 2014)
This paper presents a first approach to a state of the art on public space in Colombia. For this purpose, this article analyze the production of research groups from several universities and institutions, both, public and private. The reviewed studies are organized from the spatial, social, historical and educational perspectives and analyzed from their influence on the urban management. Finally, it is proposed to continue the traking of the development of research on the field in order to fill the gap between research and urban decisions.